Correlation Between Serum Ferritin Level and Endocrine Disorder in Female Patients with Beta-Thalassemia Major In Kerbala, Iraq - Al-khafaji, Kamal M.; AL-Mosawy, Wafaa F.; Naser, Iman H.; Almusawi, Israa M. S. (Scientific Journal of Medical Research, 2022)
Background: Beta-thalassemia major (BTM) is an inherited disorder of hemoglobin production in which there is a complete or partial failure in synthesizing ß-globin chains. Although the mainly recommended treatment for ß-TM is blood transfusion, blood transfusion leads to many toxic complications like iron overload, subsequent tissues damage, and oxidative stress. Objectives: This study aims to identify the serum ferritin levels in fifty female patients with beta-thalassemia that classified into different groups (primary, secondary amenorrhea, and normal menstruation) then examine the relationship between serum ferritin and biochemical parameters (LH, FSH, estradiol, T3, T4, and TSH). Finally, using transabdominal ultrasound to explore the size of ovaries and uterus and examine the secondary sexual characteristics in the subjects. Material and methods: This study involved fifty females with BTM aged 14-24 years. The subjects were conducted at the thalassemia branch at the Children’s teaching hospital, Karbala, Iraq. The study was carried out from July 2017 to November 2018. According to their amenorrhea status, the patients were classified into three groups: primary amenorrhea, secondary amenorrhea, and normal menstruation groups. Each female received a physical examination and a series of blood tests, and their hormone levels were studied (LH, FSH, estradiol, T3, T4, TSH, and ferritin level), along with an abdominopelvic ultrasound, and determined the changes in external secondary sexual characteristics, such as the development of the breasts, pubic and axillary hair. The relationships among these research variables were then analyzed using SAS 2012. Associations between the categorical variables were tested using the Chi-square, and Duncan’s Multiple Range, where significance was accepted at p less than 0.05. Results: The results of beta-thalassemia major patients indicate that the females significantly do not have development of breast and axillary hairs compared with those who have (p ? 0.05). We found the small size of ovaries and uterus (28, and 36% respectively) of primary amenorrhea, (2, and 4% respectively) of secondary amenorrhea and (20, and 4% respectively) of normal menstruation with remarkable significant values (p ? 0.01) between groups for both parameters. The results of LH hormone for the PA group (2.40 ± 0.36) and NM group (4.73 ± 0.75) were significantly lower (p ?.0001) than those in the SA group (7.75 ± 1.90). While the levels of estradiol hormone for PA and SA groups (22.02 ± 2.83 and 16.8 ± 3.20 respectively) were significantly decreased (p ?.001) when compared with NM groups (141.95 ± 49.75). The correlation analysis to evaluate the relationship between the LH in female beta_thalassemia major patients’ group with normal menstruation revealed a significant positive correlation with FSH and serum T3. FSH showed a significant association with T3, and T3 showed a significant positive correlation with T4 and TSH. In the female beta_thalassemia major patient group with primary amenorrhea, the data reveals a significant positive association between FSH with LH, and a negative association with the TSH, while LH showed a significant negative association with TSH. However, serum T4 indicates a significant positive correlation with serum TSH.